Analisis Kesulitan Memahami Konsep Biologi Ditinjau Dari Gaya Belajar Siswa Kelas XI IPA MAN 2 Probolinggo - Kamilia Liyana Hidayati; Ira Nurmawati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Learning biology is closely related to everyday life, so students need reasoning and conceptual understanding to solve biology problems. Students often struggle to understand biological concepts due to the extensive material and difficult Latin terms. The purpose of this research is to analyze the difficulty of students' ability to understand biological concepts on cell material by grouping students based on learning styles. This study uses a qualitative case study design. Six students from class XI IPA A were selected as subjects: two with visual learning styles, two with auditory learning styles, and two with kinesthetic learning styles. Data collection techniques included questionnaires, tests, interviews, and documentation. Qualitative analysis using the Miles, Huberman, and Saldana model involved data collection, condensation, presentation, and drawing conclusions. Students' difficulties in understanding biology concepts differentiated by learning style yielded significant results. However, differences in conceptual understanding among subjects were not uniform even though they had been categorized based on learning style. It can therefore be concluded that differences in conceptual understanding cannot be viewed solely in terms of learning style, but also in terms of other key factors such as intelligence, student focus in class, willingness to learn, and so on.